The impact of social networks as a new path of commercialization for micro entrepreneurs in Gran Asunción, Period 2004-2014 - Claudia Emilia Torres Zárate (Población y Desarrollo, 2015)
This study aims to discover the social economic impact in the Gran Asuncion Area, as a new business strategy in the sector of micro entrepreneurs, verified through the incorporation of the Internet in Paraguay, during the 2004 – 2014 decade. The social network Facebook is described, as the leading network for businesses at the present time; sequentially the ranking of the most frequented social networks, and its importance to micro entrepreneurs and consumers is presented. One of the cases with greater success in Paraguay is included as well. Lastly, the presentation and analysis of the results obtained through the surveys pursued by Internet users is developed. Therefore, through the studies conducted, the positive influence of social networks for the market of micro entrepreneurs of Asuncion metropolitan area can be demonstrated.